Manoel de Barros, ecopoet by nature - Pinheiro Cantuario, Victor Andre [UNESP] (Univ Estadual Paulista-unesp, 2020)
This article presents and discusses Manoel de Barros as an ecopoet, considering what is said by J. Scott Bryson (2002), John Bennett (2004), Ann FisherWirth and Laura-Gray Street (2013) about poetry and nature; Cheryll Glotfelty (1996) and Greg Garrard (2004) about ecocriticism, Malcolm K. McNee's (2014) considerations on Barros' poetry, the first one to write directly about the pantaneiro's work as ecopoetry, as well as Rosidelma Pereira Fraga (2014) about Barros' critical fortune, trying to build a biographical portrait and stylistic perception, observing his poetical language, the themes addressed by him, properly equated with ecopoetry characteristics and elements.
Keywords: Manoel de Barros; Ecopoetry; Contemporary Brazilian Poetry; Ecocriticism